134 Tumor-responsive, multi-functional genetically-engineered natural killer cells for immunotherapy of glioblastoma. (9th November 2020) - Wang, Jiao; Yun, Yeonhee; Pollok, Karen E; Sinn, Anthony L; Brutkiewicz, Randy R; Veronesi, Michael C; Matosevic, Sandro; Wang, Jiao
Abstract : Background: Despite aggressive treatments and care, the median survival for GBM patients is 14.6 months, which has only modestly improved over the past several decades, highlighting the need for new therapeutic approaches. NK cells, innate cytotoxic effectors, are showing potential for cancer immunotherapy for GBM. 1–3 However, tumor antigen heterogeneity and a severely immunosuppressive tumor microenvironment (TME) have rendered GBM highly resistant to most single antigen-based NK monotherapies. 4–6 Methods: To overcome these challenges, our solution has been to develop a first multifunctional immunotherapy for GBM based on genetically-engineered NK cells bearing multiple simultaneous anti-tumor functions, including local tumor responsiveness and the ability to avoid antigen escape. The activity of these lentivirally-transduced multi-functional NK (E-pNK) cells were evaluated against patient-derived GBM cells both in vitro and in vivo. Results: We have designed and synthesized a multifunctional CAR construct that expresses an anti-CD73 scFv which is cleavable by GBM-associated proteases, and a dual CAR redirected against ligands for NKG2D and GBM-associated GD2 receptors (figure 1A-B). We have isolated primary NK cells (figure 1C) and genetically manipulated them to express NKG2D, anti-GD2 scFv and anti-CD73 scFv (figure 1D-E). E-pNK cells showed a significantly higher in vitro antitumor activity towards GBM43 targets, patient-derived GBM cells, including increased percentage of tumor killing, degranulation and IFN-γ production (figure 1F-G). E-pNK cells lacking the anti-CD73 scFv following uPA treatment displayed significantly decreased killing ability of target GBM43 cells after co-culture at E/T ratios of 2.5 and 5 for 4 h (figure 1H). In addition, after treatment with cleaved anti-CD73 scFv, GBM43 cells showed a significantly reduced ability to produce adenosine due to the inhibition of CD73 enzyme activity (figure 1I). Furthermore, E-pNK cells showed potent anti-GBM activity in subcutaneously GBM43 xenografts (figure 1J-L). In vivo-adoptively transferred E-pNK cells also showed superior intratumoral infiltration into GBM43 tumors when analyzed by IHC (data not shown). Conclusions: We have generated E-pNK cells showing improved antitumor activity against GBM through increased resistance to the immunosuppressive TME via adenosinergic CD73 blockade and the simultaneous ability to specifically target GBM cells via dual CARs. Based on these results, we are currently building the orthotopic GBM mouse model to further evaluate their in vivo therapeutic effects. Acknowledgements: This work is supported, in part, by a Ralph W. and Grace M. Showalter Research Trust award and a Walther Cancer Foundation Embedding Grant. Ethics Approval: Primary human NK (pNK) cells used in this study were obtained using Purdue University's Institutional Review Board (IRB)-approved consent forms (IRB-approved protocol #1804020540). References: Sedgwick AJ, Ghazanfari N, Constantinescu P, Mantamadiotis T, Barrow AD. The role of NK cells and innate lymphoid cells in brain cancer. Front Immunol 2020;11:01549. Burger MC, Zhang CC, Harter PN, Romanski A, Strassheimer F, Senft C, et al. CAR-engineered NK cells for the treatment of glioblastoma: turning innate effectors into precision tools for cancer immunotherapy. Front Immunol 2019;10:2683. Wang J, Lupo KB, Chambers AM, Matosevic S. Purinergic targeting enhances immunotherapy of CD73+ solid tumors with piggyBac-engineered chimeric antigen receptor natural killer cells. J Immunother Cancer 2018;6:136. Lim M, Xia YX, Bettegowda C, Weller M. Current state of immunotherapy for glioblastoma. Nat Rev Clin Oncol 2018;15:422-442. Lynes JP, Nwankwo AK, Sur HP, Sanchez VE, Sarpong KA, Ariyo OI, et al. Biomarkers for immunotherapy for treatment of glioblastoma. J Immunother Cancer 2020;8:e000348. Wang J, Matosevic S. NT5E/CD73 as Correlative factor of patient survival and natural killer cell infiltration in glioblastoma. J Clin Med 2019;8:1526.